Application of Immuno-PET in Antibody–Drug Conjugate Development - Kendra S. Carmon PhD; Ali Azhdarinia PhD (Molecular Imaging, 2018)
Targeted therapies hold great promise for cancer treatment and may exhibit even greater efficacy when combined with patient selection tools. The clinical impact of identifying likely responders includes reducing the number of unnecessary and ineffective therapies as well as more accurately determining drug effects. Positron emission tomography (PET) imaging using zirconium-89 radiolabeled monoclonal antibodies (mAbs), also referred to as zirconium-89 ( 89 Zr)-immuno-PET, provides a potential biomarker to measure target expression and verify optimal delivery of targeted agents to tumors. Antibody–drug conjugates (ADCs) combine the high affinity and specificity of mAbs with the potency of cytotoxic drugs to target tumor-expressing antigen and destroy cancer cells. Thus, 89 Zr-immuno-PET of whole-body biodistribution, pharmacokinetics, and tumor targeting of antibodies and ADCs to predict toxicity and efficacy could help guide individualized treatment. Here, we review how 89 Zr-immuno-PET is being used as a companion diagnostic with the development of ADCs. Furthermore, we discuss how 89 Zr-immuno-PET may be utilized in future clinical trials as an adjunct tool with novel ADCs to select cancer patients who have the greatest potential to benefit from treatment and improve ADC dosing regimens.